Enhanced Photocatalystic Activity of TiO2/SiO2 Composite Catalysts for the Degradation of Reactive Orange 16 Under UV and Sunlight Irradiations - Vaithiyanathan, R.; Ramya, G.; Amala Infant Joice, J.; Sivakumar, T. (Asian Journal of Chemistry, 2012)
Photocatalytic decolourization and degradation of reactive orange 16 under UV and sunlight irradiations have been studied using titania catalyst synthesized via sol-gel method. As-synthesized TiO2 decolourized the dye solution completely in 130 min under UV irradiation. Under sunlight irradiation, only 25-30 % of decolourization was observed in the same irradiation time. In order to improve the efficiency of titania, TiO2/SiO2 composites of ratio 10:90, 20:80, 30:70, 40:60, 50:50 and 60:40 have been synthesized. As synthesized catalysts have been characterized by XRD and BET analyses. Their activity towards the decolourization and degradation of reactive orange 16 were studied. As synthesized TiO2-SiO2 composite catalysts showed better activity than bare TiO2. Optimization of substrate concentration, weight of catalyst and solution pH was carried out under UV irradiation. Total organic carbon analysis was carried out to determine the extent of mineralization of reactive orange 16.